An Investigation of Philosophical Thoughts in Ghani Khan Poems - Mohammad Mustafa Safa; Ezatullah Sahand (Randwick International of Education and Linguistics Science Journal, 2022)
Ghani Khan who lived from 1914-1996 is considered as one of the influential poets in Pashto literature who could speak five languages. He was a drawer and politian as well. We can imply from Ghani Khan’s several poems that he has discussed about philosophy. Ghani Khan has a passion to discuss about philosophical conceptions which philosophy talks about such as death, rationality, social values, individual freedom, and other topics. He has shown compromise to some of the Western and Eastern philosophical values hence evident from discussing in his poems. Specifically, there are signs of Western Existentialism and Eastern Sufi Metaphysics in his poetry. However, there is a contradiction in his and those of other philosophical views. Ghani views all those philosophical views according to his own view while different from those of other philosophers. For instance, believers of existentialism view life as sorrow, fright, and Nihilism whereas for Ghani Khan life is itself a joy and what he can do and should do is to spend a pleasant time. He depends everything in the universe on his lord Allah. The most important part of his view is that he considers life as a blessing from the lord thus trying to lessen the human fear from death. Consequently, most of his poetry is for the betterment of humans and establishing good relationships between them.